Farmers' Assistance Through The Learning Process in Utilizing The Potential of Local Waste Towards Organic Coffee Plantations Turekisa Village - Igniosa Taus; Victoria Ayu Puspita; Egidius Rembo; Yoseph Eduardus Nono; Maria Stefani Goo Kowe (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The people of Turekisa Village have their main profession as coffee farmers. Lectures in Turekisa Village are one way of providing learning experiences to farmer groups as partners in Community Service (PKM) activities in identifying potential and dealing with local problems in developing the village's local potential towards an organic coffee plantation in Turekisa Village.  PKM activities aim to increase the knowledge, understanding, and skills of coffee farmers in utilizing waste for managing organic coffee plantations using a thematic and andragogical participatory learning approach as a method of implementing activities. The results of the activity show that farmer groups as activity partners can increase managerial capacity farmer groups and have awareness, insight, and skills in managing coffee plantations organically by producing organic fertilizer from skin waste coffee and utilizing organic fertilizer products on coffee plantations in a sustainable manner.